2012
DOI: 10.1063/1.4767726
|View full text |Cite
|
Sign up to set email alerts
|

Energy spectra and turbulence generation in the wake of magnetic obstacles

Abstract: Numerical simulations and analysis of flow and heat transfer of an electrically conducting fluid past magnetic obstacles are reported. We studied the channel flow configuration with electrically and thermally insulated horizontal walls containing a single or multiple (two or three) magnetic dipoles. Different values of the interactive parameter 0 ≤ N ≤ 50 and with a fixed value of Re = 10 3 are simulated. Detailed insights into energy spectra and turbulence generation in the wake of magnetic obstacles are prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Therefore, they describe a decrease of the Strouhal number for increasing Hartmann number with values around St ∼ 0.1. In a similar parameter study, Kenjeres (2012)29 finds for the same interaction parameters as in our study St = 0.282 which is calculated from power spectra at several positions close to the magnetic obstacle. In the present work, the width of the area of reversed flow is used as a characteristic length of the magnetic obstacle.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, they describe a decrease of the Strouhal number for increasing Hartmann number with values around St ∼ 0.1. In a similar parameter study, Kenjeres (2012)29 finds for the same interaction parameters as in our study St = 0.282 which is calculated from power spectra at several positions close to the magnetic obstacle. In the present work, the width of the area of reversed flow is used as a characteristic length of the magnetic obstacle.…”
supporting
confidence: 81%
“…12 have termed it magnetic obstacle in analogy with the flow around a solid obstacle. Similar configurations have been investigated both experimentally and numerically 6,7,29,59,60 . The magnetic fields in these works typically had a lower degree of spatial non-uniformity, and cannot be characterized in such as simple way as a point dipole.…”
Section: Introductionmentioning
confidence: 82%
“…10 The obstruction may also take a non-solid form, such as fringing magnetic fields. [11][12][13][14] When a conducting fluid passes the localized zone of applied magnetic field, referred to as a magnetic obstacle, shear layers around the obstacle develop into time periodic vortical structures. Previous research has also shown that inhomogeneous wall conductivity may generate unstable internal shear layers and leads to a time-dependent flow similar to the wake produced behind bluff bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the imprints of the patterned turbulence structures are particularly visible in the form of quasi-periodic signals for the C d ¼ 0:1 case. Corresponding power spectra density (PSD) distributions 47 are shown in Fig. 15.…”
Section: (E)-3(h)mentioning
confidence: 99%